Pendampingan Pembuatan Nomor Induk Berusaha (NIB) Untuk Meningkatkan Kesadaran Legalitas Usaha Pelaku UMKM di Desa Tanjung Luar - Patmiwati; Baiq Dhiwanda Juniartika; Muhammad Patihin; Nova Arianti Gustiani; Saiful Fahmi; Huldiya Syamsiar (BALE LITERASI, 2026)
The low level of Business Identification Number (Nomor Induk Berusaha/NIB) ownership among Micro, Small, and Medium Enterprises (MSMEs) in Tanjung Luar Village indicates that business legality remains an issue requiring greater attention. This condition is influenced by limited understanding of the benefits of NIB, inadequate ability to use the Online Single Submission (OSS) system, and administrative challenges faced by business owners. This program aimed to improve MSMEs' understanding of the importance of business legality while providing assistance in obtaining NIB. The method employed was a descriptive qualitative approach consisting of door-to-door data collection, socialization, assistance, and evaluation. Initial data collection was conducted to identify the conditions and needs of MSME owners so that the assistance program could be implemented more effectively. The results showed that of the 26 MSMEs surveyed, 15 had not yet obtained an NIB. The socialization program was attended by 17 MSME owners, while the assistance program, followed by further support for participants facing administrative obstacles, successfully increased the number of MSMEs obtaining NIBs to 13. These findings indicate that socialization combined with initial data collection and continuous assistance effectively improved MSMEs' understanding and increased business legality ownership in Tanjung Luar Village. Therefore, the activities of data collection, socialization, and assistance in NIB registration proved effective in improving business legality among MSMEs in Tanjung Luar Village.